أثر التمكين السياسي للمرأة على أداء المجالس المنتخبة حالة المجالس المنتخبة لولاية برج بوعريريج 2012 إلى يومنا هذا - سهام عميمر (جامعة محمد بوضياف المسيلة, 2019)
تعتبر قضية المرأة ذات أهمية كبيرة على الساحة الدولية والساحة الوطنية، من خلال إبرام العديد من الاتفاقيات والمواثيق الدولية التي تدعم تعزيز وحماية حقوق المرأة لاسيما السياسية، لهذا السبب تواجه الجزائر حتمية مسايرة ومواكبة هذه التغيرات. في ضوء الدساتير الجزائرية السابقة يشير حق في الترشح دون تمييز على أساس الجنسيين، إلا انه بالنظر إلى واقع الممارسة السياسية للمرأة هناك محدودية في التمثيل على مستوى المجالس المحلية المنتخبة، وقد دفع هذا المشرع الجزائري إلى اتخاذ تدابير وإجراءات جديدة توّجت بالتعديل الدستوري لعام 2008 وما تبعه من قوانين عضوية03/12 التي تحدد كيفيات توسيع تمثيل المرأة في المجالس المحلية المنتخبة، والتي تجسد فعليا في الانتخابات التشريعية لعام 2012 التي شهدت ارتفاعا ملحوظا في عدد النائبات مقارنة بالسنوات الماضية. على الرغم من هذه الجهود التي بذلتها الحكومة الجزائرية لتفعيل دور المرأة في الحياة السياسية، فإن واقع الممارسة يظهر عكس ذلك، بسبب وجود معوقات سياسية واجتماعية واقتصادية وثقافية وحتى إعلامية حالت دون المشاركة الفعلية لها. Abstract The issue of women has been of great importance in the international arena and in the national arena ,though the conclusion of many international conventions and charters that support the promotion and protection of women’s rights especially political ones. This is why Algeria is faced with the inevitability of keeping up with these changes. In view of the previous Algerian constitutions the right to run without gender discrimination indicates that in view of the reality of women’s political practice,there is limited representation at the level of elected local councils. This prompted the Algerian legislator to take new measures and procedures that culminated in theconstitutional amendment of 2008 and followed by the membership laws of 03/12,whish set out how to expend the representation of women in elected local councils,whish is actually embodied in the legislative elections for 2012 ,wish saw a significant increase in the number of female deputies compared to previous years. Despite the efforts made by the Algerian government to activate the role of women in political life, the reality of practice shows the opposite, because of the existence of political, socio-cultural, economic, and even obstacles without actual participation.
Keywords: التمكين السياسي- المرأة -المجالس المنتخبة